Parents’ tutorial on how to keeping hands hygiene to build healthy lifestyle among children with disabilities during the covid-19 pandemic - Asri Wijiastuti; Sri Joeda Andajani; Wagino Wagino; Endang Purbaningrum; Wiwik Widajati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
Hands are the main pathways of germ transmission. Moreover, Palms are one of the sources of the COVID-19spreading particularly through touching various objects that carry the virus. People knowledge about hands washing and antiseptics are critical in preventing the transmission of the Covid-19. In particular, parents of children with total total blindnessness should have the understanding on maintaining hands hygiene to support the inhibiting and slowing the Covid-19. The aim of this study was to develop the video tutorial on healthy living habits to guide parents’ of children with total total blindnessness to teach their children to apply hands sanitizer. Therefore, parents could provide assistance for their children both at home and outside the home. This study applied the development research approach in producing video tutorial on how to accompany children with total total blindnessness to use hand sanitizer according to heath standards. The result from this study is an audio visual tutorial on how parent accompany children with total total blindnessness to use hand sanitizer that is available thorugh the link https://drive.google.com/file/d/.1j6JbPAqhu2b5yPELsyWHDV1L2b4Uy1 OM /view?usp=sharing with positive response from users. The conclusion is transmission and spreading of COVID-19disease can be minimized through frequent and careful hands hygiene for children with total total blindnessness.